Self-track Oral Ulcer Mobile Application : stoUma Artificial Intelligence (@stoUmaAI) - Wan Ahmad Kamil, Wan Nurhazirah (2022)
Self-track oral ulcer mobile application @ stoUmaAI: An innovative mobile application equipped with artificial intelligence (AI) technology features applied in the medical and dentistry world. This innovation is primarily focusing on oral ulcer pre-assessment evaluation and patient care. Oral ulceration is the most common manifestation of oral disease with pain and extreme discomfort as its clinical presentation. The COVID-19 pandemic has hindered the accessibility of routine dentistry appointments to minimize viral transmission via infected saliva. Thus, an alternative method for a patient’s pre-diagnosis evaluation and oral care of oral ulceration is urgently needed. The stoUmaAI encompasses three primary interactive interfaces; (1) general information on oral ulceration, (2) patient profile, and (3) clinician interface for feedback and advice. A user-friendly mobile app provides patients with pre-diagnosis, a built-in camera interface, and a self-monitoring interface that allows patients to keep track of their oral ulcers daily and ensures that oral health consultations can be handled remotely. Since the oral cavity is easily accessible for clinical examination, intraoral photographing can be carried out by the patients and stored in the app in seconds. Developing the Self Track Oral Ulcer Mobile Application @ stoUmaAI prototype involves the machine learning engine using Convolutional Neural Network (CNN) architecture which consists of four phases.